(untitled) (e-Journal of Linguistics, 2023)
Language is one of the important things to communicate with others. People use language to show their emotions. There are five different language styles, frozen style, formal style, consultative style, casual style, and intimate style, which people can use to interact with others. People with different social cultures, ages, statuses, and gender might use different language styles. This study investigates James Cordon’s different language style while interviewing his guest stars, James Lee Curtis, Dwayne Johnson, and Ed Sheeran, on The Late Late Show. The study results show that James Corden used three different language styles: formal, casual, and consultative. As Jamie is older than James, he prefers to use formal language during the show. However, while interviewing Dwayne and Ed Sheeran, who are younger than James, he used different language styles, casual and consultative. The results of the study indicate that the age of the addressee considers the language style preference.